1-Hexyl n-cyanoacrylate compound (Neucrylate™ AN), a new berry aneurysm treatment. I. Theoretical basis and laboratory evaluation. (4th May 2011) - Kerber, Charles W; Pakbaz, Ramin Sean
Abstract : Purpose: To develop and optimize a system for treating cerebral berry aneurysm using a new polymer based liquid embolic agent. Materials and methods: Using a variety of human corrosion casting aneurysm replicas placed in a circuit of pulsatile flowing blood, techniques were developed to optimize aneurysm filling and recreate good blood flow dynamics. As part of this effort, both experienced physicians and lay personnel were asked to treat these replicas to discover common failure modes. Additional surgically created aneurysms in dog carotid arteries were treated by experienced physicians. Results: Physicians experienced in the use of microcatheters and endovascular techniques learned to use the device effectively after, on average, five aneurysm treatments. In the dog aneurysms, all were treated to complete filling.